2016
DOI: 10.1002/aur.1687
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of visual circuit formation and refinement in a mouse model of autism

Abstract: Aberrant connectivity is believed to contribute to the pathophysiology of autism spectrum disorder (ASD). Recent neuroimaging studies have increasingly identified such impairments in patients with ASD, including alterations in sensory systems. However, the cellular substrates and molecular underpinnings of disrupted connectivity remain poorly understood. Utilizing eye‐specific segregation in the dorsal lateral geniculate nucleus (dLGN) as a model system, we investigated the formation and refinement of precise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 80 publications
(152 reference statements)
0
14
0
Order By: Relevance
“…Inter-hemispheric connectivity was found to be present (synchronous rsfMRI signal) in the area of the visual cortex, but detailed analysis employing recombinant rabies virus tracing found no evidence for monosynaptic connections between the two hemispheres in this region. A recent work by Cheng and collaborators (2016) showed, however, that the patterning of retinal fibers within the dorsal lateral geniculate nucleus of both neonatal and adult BTBR mice was disrupted, with a much higher degree of overlap of ipsi- and contralateral fibers, than in B6 mice. Generally, however, aberrations in ipsilateral connections were found in the fronto-cortical regions, but not in the posterior parts of the cortex, and for subcortical fronto-thalamic and striatal fibers.…”
Section: Neuroanatomy Of the Btbr Mouse: Impaired Axon Guidance Anmentioning
confidence: 96%
“…Inter-hemispheric connectivity was found to be present (synchronous rsfMRI signal) in the area of the visual cortex, but detailed analysis employing recombinant rabies virus tracing found no evidence for monosynaptic connections between the two hemispheres in this region. A recent work by Cheng and collaborators (2016) showed, however, that the patterning of retinal fibers within the dorsal lateral geniculate nucleus of both neonatal and adult BTBR mice was disrupted, with a much higher degree of overlap of ipsi- and contralateral fibers, than in B6 mice. Generally, however, aberrations in ipsilateral connections were found in the fronto-cortical regions, but not in the posterior parts of the cortex, and for subcortical fronto-thalamic and striatal fibers.…”
Section: Neuroanatomy Of the Btbr Mouse: Impaired Axon Guidance Anmentioning
confidence: 96%
“…BTBR mice display deficits in social interaction and communication assays and exhibit repetitive and stereotyped behaviors. During the relatively short time since its discovery as an ASD model, the BTBR strain has been increasingly used to study the etiology and to uncover potential interventions for ASD (Moy et al, 2007 ; McFarlane et al, 2008 ; Llaneza et al, 2010 ; Ruskin et al, 2013 ; Cheng et al, 2016 ; Mychasiuk and Rho, 2016 ; Newell et al, 2016 ). Ruskin and colleagues reported that the BTBR mice showed decreased sociability in the three-chamber test, decreased self-directed repetitive behavior, and improved social communication in a food preference assay after being fed a KD (Ruskin et al, 2013 ).…”
Section: Metabolic Therapy and Asd—evidence From Animal Modelsmentioning
confidence: 99%
“…However, atypical sensory reactivity represents early markers of autism and are predictive of social-communication deficits and repetitive behaviors in childhood. Although recent findings performed in mouse ASD genetic models report sensory deficits(Chelini et al, 2019; Cheng et al, 2017; Drapeau et al, 2018; Huang et al, 2019; Orefice et al, 2016; Siemann et al, 2017), they were explored during juvenile or adult period. Whether sensory dysfunctions might be present at the early life stage is something unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Much of research in animal models of syndromic and non-syndromic forms of ASDs has focused on the social and cognitive difficulties and their underlying mechanisms (Robertson and Baron-Cohen, 2017). Recent increasing evidences suggest that sensory traits such as tactile, visual, auditory, olfactory, gustatory and heat abnormalities (Chelini et al, 2019; Cheng et al, 2017; Drapeau et al, 2018; Huang et al, 2019; Orefice et al, 2016; Siemann et al, 2017) are present in ASD models, yet the existence of sensory dysfunctions during early life period have been unexplored.…”
Section: Introductionmentioning
confidence: 99%